2002
DOI: 10.1034/j.1600-0714.2002.310402.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin‐6 level is a useful marker in evaluating therapeutic effects of levamisole and Chinese medicinal herbs on patients with oral lichen planus

Abstract: We conclude that levamisole and levamisole plus Chinese medicinal herbs can modulate the serum IL-6 level in OLP patients. IL-6 may be a useful marker in evaluating therapeutic effects and in monitoring the disease status of OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 25 publications
5
81
0
1
Order By: Relevance
“…In previous studies of patients with oral lichen planus, serum and salivary IL-6 levels were decreased significantly at a mean 42 days and 0.5-3 months (15-90 days) after treatment. 12,31 We cannot compare these results with ours due to different patient characteristics. However, we cannot deny the possibility that the salivary concentrations of IL-6 might have come down to the levels of controls, if we had collected saliva from the OSCC patients at the time of 2-3 months after treatment.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In previous studies of patients with oral lichen planus, serum and salivary IL-6 levels were decreased significantly at a mean 42 days and 0.5-3 months (15-90 days) after treatment. 12,31 We cannot compare these results with ours due to different patient characteristics. However, we cannot deny the possibility that the salivary concentrations of IL-6 might have come down to the levels of controls, if we had collected saliva from the OSCC patients at the time of 2-3 months after treatment.…”
Section: Discussionmentioning
confidence: 77%
“…IL-6 is produced by various cells types, including lymphoid cells, monocytes, fibroblasts, endothelial cells, oral epithelial cells, and several types of tumor cells. 8, 10, 11 Sun et al 12 suggested that IL-6 was produced by SCC, and contributed to the progression of the disease. We could not measure the serum levels of IL-6 in the patients and controls in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…В механизме развития ПЛ СОР большое значение играют иммунные нарушения [19,33,44,63,81,88,121,128,150,159,163].…”
unclassified